Implementation of Microlearning to Improve Learning Outcomes on Digital Number System Material - Iqbal, Muhammad; Pramudyanti; rinaldi, Daniel (Jurnal PPS-TP: Jurnal Pendidikan Analisis, Aplikasi Teori dan Hasil Penelitian, 2025)
This study aims to determine the effectiveness of microlearning implementation on the topic of Digital Number Systems in improving student learning outcomes. The research employed a quantitative approach with a quasi-experimental design of the Nonequivalent Control Group Design type. The research subjects were students of class X TKJ 1 as the experimental group and X TKJ 2 as the control group at SMK Muhammadiyah 2 Kalirejo. The research instrument consisted of pretest and posttest to measure students’ cognitive learning outcomes. Data analysis was conducted using the Wilcoxon Signed Rank Test, Mann-Whitney U Test, and N-Gain calculation. The results showed a significant improvement in learning outcomes in both groups (Asymp. Sig = 0.000), with a significant difference between the experimental and control groups (Asymp. Sig = 0.017). The average N-Gain in the experimental group was 71.68 (high category), while in the control group it was 46.48 (moderate category). Thus, microlearning was proven to be more effective in improving students’ learning outcomes compared to conventional learning methods.